Dietary Pattern of Schoolgoing Adolescents in Urban Baroda, India (Journal of Health, Population and Nutrition, 2014)
Diet plays a very important role in growth and development of adolescents, during which the development of healthy eating habits is of supreme importance. There is a dual burden of undernutrition and overnutrition in this age-group. The study assessed the food habits, food preferences, and dietary pattern of schoolgoing urban adolescents in Baroda, India. Both quantitative and qualitative methods were used in this study. A quantitative survey was carried out using a pre-tested self-administered structured questionnaire among 1,440 students from class 6 to 12 in 7 English medium and 23 Gujarati medium schools. Focus group discussions, 5 each with adolescent boys and girls, were held, along with 5 focus group discussions with teachers of Gujarati and English medium schools. Nearly 80% of adolescents had consumed regular food, like dal, rice, chapati, and vegetables, including green leafy vegetables. Nearly 50% of them had consumed chocolates, and about one-third consumed fast foods. Nearly 60% of adolescents had their breakfast daily while the remaining missed taking breakfast daily. Nearly one-third of adolescents were missing a meal once or twice a week. A large majority had consumed regular foods. However, more than half of them had consumed chocolates, soft drinks, and over one-third had taken fast foods. DOI: http://dx.doi.org/10.3329/jhpn.v31i4.20047 J HEALTH POPUL NUTR 2013 Dec; 31(4): 490-496